"Our biggest killer": multimodal discourse representations of dementia in the British press. Issue 3 (27th May 2018) - Brookes, Gavin; Harvey, Kevin; Chadborn, Neil; Dening, Tom
ABSTRACT: A recent (2016) Office for National Statistics report stated that dementia is now "the leading cause of death" in England and Wales. Ever fixated with the syndrome (an unfailingly newsworthy topic), the British press was quick to respond to the bulletin, consistently headlining that dementia was the nation's "biggest killer, " while (re)formulating other aspects of the report in distorting and emotive metaphorical terms. In this paper we examine how the media, through use of a recurring set of linguistic and visual semiotic tropes, portrayed dementia as an agentive entity, a "killer, " which remorselessly attacks its "victims." Such a broadly loaded and sensationalist representation, we argue, not only construed dementia as a direful and pernicious disease, but also, crucially, obscured the personal and social contexts in which the syndrome is understood and experienced (not least by people with dementia themselves). This intensely lurid type of representation not only fails to address the ageist misinformation and common misunderstandings that all too commonly surround dementia, but is also likely to exacerbate the stress and depression frequently experienced by people with dementia and their families.